Varicose remodeling of veins is suppressed by 3‐hydroxy‐3‐methylglutaryl coenzyme a reductase inhibitors - Eschrich, Johannes Roland; Meyer, Ralph; Kuk, Hanna; Wagner, Andreas H.; Noppeney, Thomas; Debus, Sebastian; Hecker, Markus; Korff, Thomas (Journal of the American Heart Association, 2016)
BackgroundDespite the high prevalence of chronic venous insufficiency and varicose veins in the Western world, suitable pharmaceutical therapies for these venous diseases have not been explored to date. In this context, we recently reported that a chronic increase in venous wall stress or biomechanical stretch is sufficient to cause development of varicose veins through the activation of the transcription factor activator protein 1.Methods and ResultsWe investigated whether deleterious venous remodeling is suppressed by the pleiotropic effects of statins. In vitro, activator protein 1 activity was inhibited by two 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitors, rosuvastatin and atorvastatin, in stretch‐stimulated human venous smooth muscle cells. Correspondingly, both statins inhibited venous smooth muscle cell proliferation as well as mRNA expression of the activator protein 1 target gene monocyte chemotactic protein 1 (MCP1). In isolated mouse veins exposed to an increased level of intraluminal pressure, statin treatment diminished proliferation of venous smooth muscle cells and protein abundance of MCP1 while suppressing the development of varicose veins in a corresponding animal model by almost 80%. Further analyses of human varicose vein samples from patients chronically treated with statins indicated a decrease in venous smooth muscle cell proliferation and MCP1 abundance compared with samples from untreated patients.ConclusionsOur findings imply that both atorvastatin and rosuvastatin effectively inhibit the development of varicose veins, at least partially, by interfering with wall stress-mediated activator protein 1 activity in venous smooth muscle cells. For the first time, this study reveals a potential pharmacological treatment option that may be suitable to prevent growth of varicose veins and to limit formation of recurrence after varicose vein surgery.
Gesehen am 29.05.2020